1997
DOI: 10.1093/ije/26.4.797
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization of aboriginal and non-aboriginal patients for respiratory tract diseases in Western Australia, 1988-1993

Abstract: Admission rates for respiratory conditions were consistently higher among the Aboriginal population and in non-metropolitan areas. The overwhelming importance of infections among Aboriginal admissions has significant implications for the prevention and management of respiratory diseases among Aboriginal people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
35
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 25 publications
6
35
1
Order By: Relevance
“…8,9 Socioeconomic and biological factors may be important determinants of risk. Skin, respiratory and ear infections occur more commonly in Aboriginal communities, 18 and as many of these infections are treated empirically with broad-spectrum antibiotics, resultant antimicrobial selection pressure may drive the emergence of antibiotic-resistant organisms. MRSA bacteraemia was also associated with geriatric unit admission.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Socioeconomic and biological factors may be important determinants of risk. Skin, respiratory and ear infections occur more commonly in Aboriginal communities, 18 and as many of these infections are treated empirically with broad-spectrum antibiotics, resultant antimicrobial selection pressure may drive the emergence of antibiotic-resistant organisms. MRSA bacteraemia was also associated with geriatric unit admission.…”
Section: Discussionmentioning
confidence: 99%
“…In an indigenous rural community in Western Australia, BREMNER et al [5] described a high prevalence (24%) of wheeze in female patients v18 yrs of age. WILLIAMS et al [18] reported that in Western Australia, where indigenous status has been collected as part of the hospital record for several years, the admission rate for asthma was higher for indigenous than nonindigenous children (rate ratios for indigenous versus nonindigenous children ranged 1.4 -5.3). While hospitalization data are not good proxy for prevalence and accuracy is questionable, at the very least, the Western Australian data suggest that serious asthma requiring hospitalization is more common among indigenous children.…”
Section: Discussionmentioning
confidence: 99%
“…The high proportions of ␤-lactamase production most likely reflected exposure of this group to antibiotics. Respiratory disease and otitis media are significant health problems in the Aboriginal Australian population (14,26). Pneumococci are the biggest cause of pneumonia and otitis media in this population, and recommended therapies are penicillin G and amoxicillin, respectively (8,26).…”
mentioning
confidence: 99%